2017
DOI: 10.1111/1475-6773.12668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Provider Competition under Global Budgeting on the Use of Cesarean Delivery

Abstract: While global budgeting is an effective cost containment tool, intensified financial pressures may lead to unintended consequences of compromised quality due to a shift in provider practice in pursuit of financial rewards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Additionally, medical expenditure dropped sharply after the GBPS was fully implemented, whereas the GBPS pilot showed no statistically significant changes. Previous research also showed that the GBPS had a more prominent impact in changing physician behavior in larger general hospitals [32,34]. This may be because tertiary hospitals have more methods to control for expenditure, such as shifting inpatients to secondary and primary hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, medical expenditure dropped sharply after the GBPS was fully implemented, whereas the GBPS pilot showed no statistically significant changes. Previous research also showed that the GBPS had a more prominent impact in changing physician behavior in larger general hospitals [32,34]. This may be because tertiary hospitals have more methods to control for expenditure, such as shifting inpatients to secondary and primary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Tertiary hospitals in Shanghai make up 70.87% of the total medical expenditure among healthcare institutions. Based on the theory of expected income, they consequently have a greater ability to undertake loss associated with the GBPS [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The total actual reimbursement to Hospital A is then $1.9 million ($1 million + 0.6 * $1.5 million) and to Hospital B is $2.1 million ($1.5 million + 0.6 * $1 million). Thus, although hospitals competing for a share of the GBS will have an incentive to overprovide all services (Chen, Chen, & Liu, 2018;Chen & Fan, 2015;Fan, Chen, & Kan, 1998;Hsu, 2014), this incentive may be particularly strong for sheltered services, given their fixed reimbursement rates.…”
Section: Sheltered Services Within a Global Budgetmentioning
confidence: 99%
“…The existing researches on RGB-FPS have some limitations. First, many studies focus on the micro performance of diseases but less on the macro performance of hospitals after the implementation of RGB-FPS [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Theoretical and empirical studies have revealed that RGB-FPS may lead hospitals to increase service volume by attracting patients from other hospitals and hospitalization decomposition [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%